2004
DOI: 10.1038/sj.pcan.4500696
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis and patient satisfaction following octant transrectal ultrasound-guided prostate biopsy: a prospective study comparing consultant urologist, specialist registrar and nurse practitioner in urology

Abstract: Transrectal ultrasound-biopsy of prostate whether performed by nurse practitioner or urologist is equally reliable if adequate training is provided. Patients are happy to undergo prostate biopsy and receive information about the diagnosis from an appropriately trained prostate cancer nurse specialist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 4 publications
1
30
0
Order By: Relevance
“…As the health care landscape continues to change, so does the role of NPs, and a growing body of literature has highlighted their role and functions [27][28][29][30][31]. In general, existing studies suggest that patient satisfaction with the quality of care provided by NPs is equal to or higher than patient satisfaction with quality of care provided by physicians [32][33][34][35]. Research on patient satisfaction among the elderly and NPs is relatively limited.…”
Section: Discussionmentioning
confidence: 98%
“…As the health care landscape continues to change, so does the role of NPs, and a growing body of literature has highlighted their role and functions [27][28][29][30][31]. In general, existing studies suggest that patient satisfaction with the quality of care provided by NPs is equal to or higher than patient satisfaction with quality of care provided by physicians [32][33][34][35]. Research on patient satisfaction among the elderly and NPs is relatively limited.…”
Section: Discussionmentioning
confidence: 98%
“…Rates of cancer detection and biopsy-related complications were similar for nurses and consultants performing prostate biopsy. 5,35,36 Improved continuity of care has also been identified as a positive outcome of nurses performing prostate biopsies. Furthermore, appropriately trained and experienced nurses would be suitable provi ders of prostate biopsy technique training for urology trainees.…”
Section: Competing Interestsmentioning
confidence: 98%
“…Patients receiving care as part of this programme are monitored closely by the nurse practitioner, who promotes healthy lifestyle behaviours, including dietary advice, e xercise, and smoking cessation. 34 Diagnostic testing by nurses In 2004, Henderson et al 5 performed a study in which patients were offered the choice of having a diagnostic procedure performed by a nurse rather than by a medical practitioner; when given this option, 18% preferred the nurse. An audit of a nurse-led clinic for suspected prostate cancer found that 84% of patients were happy for the nurse to give them the biopsy results.…”
Section: Competing Interestsmentioning
confidence: 99%
See 2 more Smart Citations